Kebijakan Pemerintah Dalam Pemanfaatan Gas Suar Yang Terproduksi Dari Sumur Minyak (Associated Gas) Dalam Mendukung Program Net Zero Emission - Petrus Krisologus; Sugianto Sugianto (Strata Law Review, 2023)
In line with the 2015 Paris Climate Agreement which aims to reduce environmental pollution that has the potential to cause global warming, the Government of Indonesia has launched a net zero emission (NZE) target in year 2060 as a response to facing challenges and climate change in the future. There are many efforts to reduce carbon emissions one of them is the use of gas flares, therefore the Government of Indonesia has issued Regulation of the Minister of Energy and Mineral Resources Number 31 of 2012 concerning Implementation of Flaring Gas (Flaring) in Oil and Gas Business Activities, and its amendment. This paper is written and limited to activities in the upstream oil and gas sector and to see the comptability between regulations related to the implementation of the usage of gas flares with oil and gas production sharing contracts between the State and Cooperation Contract contractors (KKS Contractors). This research was made based on literature review and its application in oil and gas and industry, found the comptability effort to encourage the oil and gas player to use flare gas optimally considering the economics of contractor.